2021
DOI: 10.1016/j.ajic.2021.04.079
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 vaccine acceptance, hesitancy, and refusal among Canadian healthcare workers: A multicenter survey

Abstract: Background : Determinants of COVID-19 vaccine acceptance among healthcare workers (HCW) remains poorly understood. We assessed HCWs’ willingness to be vaccinated and reasons underlying hesitancy. Methods : Cross-sectional survey across 17 healthcare institutions. HCWs eligible for vaccination (Pfizer-BioNTech mRNA) in December 2020 were invited to receive immunization. Multivariate logistic regression was performed to identify predictors of acceptance. Reasons for refus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
190
17
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(269 citation statements)
references
References 19 publications
25
190
17
7
Order By: Relevance
“…On the one hand, such results are clearly consistent with the health belief model, i.e., an individual’s belief in a health threat, as well as belief in the effectiveness of the recommended health behavior or action are the main predictors for the likelihood that the person will adopt the behavior [ 46 ]. On the other hand, we failed to identify, as a predictive for acceptance of the mandatory status, a series of factors that previous studies strongly associated with the acceptance of SARS-CoV-2/COVID-19 vaccines, i.e., gender, history of personal uptake of SIV, knowledge status, previous interactions with the pathogen [ 47 , 48 , 49 ]. However, it should be stressed that the willingness to pay for a vaccine may be considered a summary index for perceived ease of access, awareness of the vaccine (including a trade-off of perceived pros and cons), but also the ability to pay for the vaccine [ 50 ].…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…On the one hand, such results are clearly consistent with the health belief model, i.e., an individual’s belief in a health threat, as well as belief in the effectiveness of the recommended health behavior or action are the main predictors for the likelihood that the person will adopt the behavior [ 46 ]. On the other hand, we failed to identify, as a predictive for acceptance of the mandatory status, a series of factors that previous studies strongly associated with the acceptance of SARS-CoV-2/COVID-19 vaccines, i.e., gender, history of personal uptake of SIV, knowledge status, previous interactions with the pathogen [ 47 , 48 , 49 ]. However, it should be stressed that the willingness to pay for a vaccine may be considered a summary index for perceived ease of access, awareness of the vaccine (including a trade-off of perceived pros and cons), but also the ability to pay for the vaccine [ 50 ].…”
Section: Discussioncontrasting
confidence: 70%
“…For example, in the study by Janssen et al, the willingness to get vaccinated against COVID-19 was 53.2%, but 19.8% and 14.1% were either not likely or not willing to get vaccinated at all [ 59 ], while a report by Gharpure et al showed that a median of 37.5% of participating long-term care staff from the United States had accepted the first shot of a COVID-19 vaccine at the time of the study, demonstrating a low response to the vaccination campaign [ 60 ]. Moreover, even in the aforementioned study from Verger et al a more accurate analysis of reported data identified some degree of vaccine hesitancy in 28.4% of respondents [ 47 , 48 ]. As HCWs represent a model for the general public, they may either be instrumental in overcoming vaccine hesitancy [ 61 ], or improperly spread false beliefs and misconceptions that may be eventually detrimental to global efforts to achieve high vaccination rates as soon as possible [ 12 , 13 , 32 , 34 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrary to our ndings, Dzieciolowska et al found that the level of COVID-19 vaccine was higher among Canadian physicians aged more than 50 years, while they agreed with ours regarding the gender of physicians with high vaccine acceptance (Dzieciolowska et al 2021). Also, Shekhar et al 2021 in the United States reported gures that contradict our age group of physicians with high vaccine acceptance.They found that the acceptance of vaccination against COVID-19 increased with increasing age as 47% aged more than 70 years old.…”
Section: Discussioncontrasting
confidence: 82%
“…A lower percent of vaccine refusal was reported in the United States, as Shekhar et al, in their study reported that only 8% of HCWs refused to be vaccinated, with a higher percentage of them accepted to take the vaccine (36%) while the greatest percent was the HCW who waited for a review before being vaccinated (56%) (Shekhar et Also, in Canada and Belgium, the level of COVID-19 vaccine acceptance was high in 48.6% of the physicians, 23 % showed moderate acceptance while only 28.4% showed hesitancy towards vaccination (Verger P et al2021). A much higher rate of physicians' acceptance was recorded by an Canadian study, as Dzieciolowska et al, found that 80.9% accepted to take the vaccine while only 19.1% refused (Dzieciolowska et al 2021).…”
Section: Discussionmentioning
confidence: 94%